Association of kisspeptin gene (KISS1) with litter size in migratory Gaddi goats in western Himalayan state of Himachal Pradesh - SANKHYAN, VARUN; THAKUR, Y P; DOGRA, PARDEEP KUMAR (The Indian Journal of Animal Sciences, 2020)
Migratory goat farming, practiced by nomadic communities is common in Himalayan regions. Gaddi also known as ‘White Himalayan goat’ is the predominant goat breed constituting 60–65% of total goats in the state. The Kisspeptin gene (KISS1) that encodes kisspeptin protein is considered to be a candidate gene affecting multiple birth in goats. The present study was carried out to identify polymorphism at kisspeptin (KISS1 gene) and its association with litter size in migratory Gaddi goat. Polymorphism of KISS1 gene was investigated in Gaddi goats (89) using PCR-RFLP and DNA sequencing approach. PCR-RFLP analysis at KISS1 locus revealed 3 different genotypes, viz. AA with undigested one fragment at 377 bp, TT with two digested fragments at 256 and 121 bp, and AT with three fragments at 377, 256 and 121 bp. The frequencies of AA, AT and TT genotypes were 0.17, 0.52 and 0.31, respectively while the frequency of A and T alleles was 0.43 and 0.57. AT genotype was predominant genotype while AA genotype was having least frequency among the goats screened. The observed allele number (No) and effective allele number (Ne) were 2 and 1.96, respectively. Observed heterozygosity (Hobs), expected heterozygosity (Hexp) and PIC values estimated were 0.52, 0.49 and 0.37, respectively. Hobs and PIC values indicated that sufficient genetic variation exist at the locus. Sequencing of representative sample of different genotypes confirmed presence of SNP (T125A) as detected by PCR-RFLP. The mean litter size for animals belonging to AA, AT and TT genotypes were 1.12±0.08, 1.34±0.11 and 1.73±0.15 kids, respectively. Significant association of genotypes was observed with litter size in Gaddi goat. The study detected association between allele T in KISS1 gene and litter size. Study on additional data based on more number of animals in diversified flocks should be carried out for validation of the preliminary findings.